The Effect of Teaching Strategies and Cognitive Style on Reading Comprehension - Marlin Helentina Napitupulu; Lince Sihombing; Berlin Sibarani (LINGUISTIK TERAPAN, 2015)
The objectives of this study were to examine whether (1) the students’ achievement on reading comprehension taught by using CSR Strategy is higher than that of taught by using REAP Strategy, (2) reading comprehension achievement of reflective cognitive style is higher than reading comprehension achievement of impulsive cognitive style, and (3) there is interaction between teaching strategies and cognitive styles on students’ achievement on reading comprehension. This study was conducted by using experimental research with factorial design 2X2. The data were analyzed by using Two-Way ANOVA. Based on the analysis, there were found that (1) CSR and REAP strategy significantly affect students’ achievement on reading comprehension, students’ achievement on reading comprehension taught by using CSR is higher than that of the students’ taught by using REAP; (2)the achievement on reading comprehension of the students with reflective cognitive style is higher than that of the students with impulsive cognitive style; and (3) there is an interaction between teaching strategies and cognitive style on students’ reading comprehension achievement. It showed that students who read with reflective cognitive style got higher result than students who read with impulsive cognitive style if they were taught by CSR, and students who read with reflective cognitive style got higher  result than students who read with impulsive reflective style if they were taught by REAP. Key words: cognitive style; reading comprehension; and teaching strategies